2017
DOI: 10.4103/jehp.jehp_97_15
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the levels anxiety, self-perception of preparation and expectations for success using an objective structured clinical examination, a written examination, and a preclinical preparation test in Kerman dental students

Abstract: STATEMENT OF THE PROBLEM:Examinations have an important role in evaluating students’ learning outcomes and their mastery of a subject. Passing or failing an examination can have far-reaching consequences for the students. Therefore, it is not surprising that international studies consistently show that dental students report examinations and grades among the highest ranking stressors in dental schools.PURPOSE:The aim of this research was to measure the levels of anxiety, self-perception of preparation and expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…Some authors have assessed the students' anxiety level when faced with the OSCE and other exams, such as the written test and traditional pre-clinical practical exam, and have found moderate to high levels of anxiety in all exams, with higher values for OSCE, but not related to performance in the exams. 10,22 In another study, 79% of students said they were afraid of performing the task when being assessed by a faculty member. 23 One study assessed the usefulness of a game (OSCEGame) to familiarize students with the procedures and reduce anxiety as a preparation for the OSCE and concluded that it was a useful and efficient online tool in terms of preparation, especially for inexperienced students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have assessed the students' anxiety level when faced with the OSCE and other exams, such as the written test and traditional pre-clinical practical exam, and have found moderate to high levels of anxiety in all exams, with higher values for OSCE, but not related to performance in the exams. 10,22 In another study, 79% of students said they were afraid of performing the task when being assessed by a faculty member. 23 One study assessed the usefulness of a game (OSCEGame) to familiarize students with the procedures and reduce anxiety as a preparation for the OSCE and concluded that it was a useful and efficient online tool in terms of preparation, especially for inexperienced students.…”
Section: Discussionmentioning
confidence: 99%
“…9 The OSCE is believed to be capable of inducing a higher level of anxiety than other assessment formats, as there is a constant observation by the evaluators. 10 Therefore, parallel assessment focused on this psychological aspect of anxiety is important.…”
Section: Introductionmentioning
confidence: 99%
“…Kekuatan korelasi yang lemah dengan arah korelasi negatif menunjukkan bahwa semakin baik faktor ujian maka semakin rendah skor kecemasannya. Penelitian yang dilakukan oleh Kalantari et al 13 menunjukkan metode OSCE menyebabkan tingkat kecemasan paling tinggi dibandingkan metode ujian lainnya (p = 0.04). 13 Tidak seperti ujian tertulis yang tidak memberikan batasan waktu untuk setiap soal dan mahasiswa dapat kembali ke soal tertentu di akhir ujian setelah mengerjakan soal lainnya, dalam suatu OSCE setiap soal atau stasiun memiliki durasi waktu yang telah ditentukan dan tidak dapat diperpanjang.…”
Section: Pendahuluanunclassified
“…Penelitian yang dilakukan oleh Kalantari et al 13 menunjukkan metode OSCE menyebabkan tingkat kecemasan paling tinggi dibandingkan metode ujian lainnya (p = 0.04). 13 Tidak seperti ujian tertulis yang tidak memberikan batasan waktu untuk setiap soal dan mahasiswa dapat kembali ke soal tertentu di akhir ujian setelah mengerjakan soal lainnya, dalam suatu OSCE setiap soal atau stasiun memiliki durasi waktu yang telah ditentukan dan tidak dapat diperpanjang. Jika mahasiswa tidak dapat menjawab soal di satu stasiun maka tidak ada waktu lain untuk mengerjakan selain di stasiun tersebut.…”
Section: Pendahuluanunclassified
“…[ 5 ] For example, an event such as an examination may be perceived as stressful by some students and nonstressful by some. [ 6 ] This perception depends on the availability of resources and elements in their surroundings such as class notes, books, helpful friends, friendly faculty, and mental preparedness for the examination. Not surprisingly, mental health was found to be a prevalent health issue among dental students.…”
Section: Introductionmentioning
confidence: 99%